THE EFFECT OF ROLE CONFLICT, WORKLOAD AND WORK STRESS ON PERFORMANCE OF EMPLOYEE AGENCY AND HUMAN RESOURCES DEVELOPMENT IN KOTA PARIAMAN - Suhelmi Helia; Dafit Ardi; Benny Armiyuza; Desmarwan Desmarwan (SEAN Institute, 2022)
This study aims to (1) Knowing the effect of role conflict on the performance of BKPSDM employees in Pariaman City. (2) Knowing the effect of workload on the performance of BKPSDM employees in Pariaman City. (3) Knowing the effect of work stress on the performance of BKPSDM employees in Pariaman City. (4) Knowing the effect of role conflict, workload and work stress together on the performance of Pariaman City BKPSDM employees. The population and sample in this study were all BKPSDM employees of Pariaman City as many as 32 people. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity. ResultsThis study shows that (1) Role conflict has a significant negative effect on the performance of BKPSDM employees in Pariaman City. (2) Workload has a significant negative effect on the performance of BKPSDM employees in Pariaman City. (3) Job stress has a significant negative effect on the performance of BKPSDM employees in Pariaman City. (4) Role conflict, workload and work stress together have a significant negative effect on the performance of Pariaman City BKPSDM employees.